2009
DOI: 10.1091/mbc.e08-09-0985
|View full text |Cite
|
Sign up to set email alerts
|

MCAK and Paclitaxel Have Differential Effects on Spindle Microtubule Organization and Dynamics

Abstract: Within the mitotic spindle, there are multiple populations of microtubules with different turnover dynamics, but how these different dynamics are maintained is not fully understood. MCAK is a member of the kinesin-13 family of microtubule-destabilizing enzymes that is required for proper establishment and maintenance of the spindle. Using quantitative immunofluorescence and fluorescence recovery after photobleaching, we compared the differences in spindle organization caused by global suppression of microtubul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 87 publications
3
51
0
1
Order By: Relevance
“…These data provide a molecular link between the chromosomal MTs and the K-fibers that goes beyond previous observations of the formation of acentrosomal MTs at the kinetochores (Khodjakov et al, 2003;Maiato et al, 2004). Interestingly, the distinct spindle MT subclasses have distinct dynamic properties, (Rizk et al, 2009), and functional studies have shown that MCRS1 could have a role in the regulation of Kfiber minus-end stability (Meunier and Vernos, 2011).…”
Section: Kidmentioning
confidence: 50%
“…These data provide a molecular link between the chromosomal MTs and the K-fibers that goes beyond previous observations of the formation of acentrosomal MTs at the kinetochores (Khodjakov et al, 2003;Maiato et al, 2004). Interestingly, the distinct spindle MT subclasses have distinct dynamic properties, (Rizk et al, 2009), and functional studies have shown that MCRS1 could have a role in the regulation of Kfiber minus-end stability (Meunier and Vernos, 2011).…”
Section: Kidmentioning
confidence: 50%
“…First, extended treatment (24 hours) of PtK cells with nanomolar concentrations of taxol was recently reported to reduce kinetochore fiber fluorescence intensity suggesting that taxol can compromise microtubule attachment (Rizk et al, 2009). A second drawback is that the three cited observations that support this theory were made in different cell types (HeLa or PtK cells) with variable concentrations of taxol (1 mM versus 10 mM).…”
Section: The Case For Intrakinetochore Stretch As a Sac Regulatormentioning
confidence: 99%
“…MTs in kif2a −/− cells frequently fail to stop growing after reaching the cell edge, resulting in bent and overextended MTs; this suggests that Kif2A promotes catastrophes at the cell cortex. During mitosis, different kinesin-13 family members share the workload: whereas Kif2A and Kif2B are primarily associated with the centrosome, Kif2C/MCAK predominates at the kinetochores [64,65]; therefore these proteins are likely to affect diverse MT subpopulations differently ( [5] and references therein).…”
Section: Regulating Mt Disassemblymentioning
confidence: 99%
“…Free MT ends can elongate or shorten, and even mild suppression of MT dynamics by low doses of MT-stabilizing or -destabilizing drugs has a profound effect on the organization of the mitotic apparatus, directional migration and even synaptogenesis in neuronal cells [5][6][7]. Cells express an arsenal of MT-modulating factors, some of which promote assembly [such as XMAP215 (Xenopus microtubule-associated protein 215)] or disassembly [kinesin-13s and stathmin/SCG10 (superior cervical ganglion-10 protein) proteins], while others have more specific roles only on a subset of MTs.…”
Section: Introductionmentioning
confidence: 99%